Contemporary Guidelines for the Treatment and Prevention of Nosocomial Infections: Critical Analysis and Practical Perspectives. - Aferdita Ademi; Shpetim Qyra; Ferizat Dika-Haxhirexha; Agron Dogjani; Petrit Biberaj; Kastriot Haxhirexha (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Nosocomial infections remain a significant threat to patient safety worldwide, driving morbidity, mortality, and escalating healthcare costs. Despite comprehensive guidelines from the WHO, CDC, and ECDC, variability in recommendations and persistent implementation gaps impede optimal uptake.